2000
DOI: 10.1074/jbc.275.4.2255
|View full text |Cite
|
Sign up to set email alerts
|

Association of Heterotrimeric Gi with the Insulin-like Growth Factor-I Receptor

Abstract: The insulin-like growth factor-I receptor (IGF-IR) is a key regulator of cell proliferation and survival. Activation of the IGF-IR induces tyrosine autophosphorylation and the binding of a series of adaptor molecules, thereby leading to the activation of MAPK. It has been demonstrated that pertussis toxin, which inactivates the G i class of GTP-binding proteins, inhibits IGF-I-mediated activation of MAPK, and a specific role for G ␤␥ subunits in IGF-I signaling was shown. In the present study, we have investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
53
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 56 publications
10
53
0
Order By: Relevance
“…The first proposal is that the receptors possess the ability to directly catalyze heterotrimeric G protein guanine nucleotide exchange (32). Consistent with this, several groups have reported that heterotrimeric G protein subunits co-precipitate with the IGF-1 and insulin receptors (22,23,25) or have demonstrated that small peptides derived from the insulin and IGF-2 receptors promote a mastoparan-like acceleration of GTP exchange on purified heterotrimeric G proteins in vitro (31,(33)(34)(35). The second model advanced to explain heterotrimeric G protein-dependent signaling by non-GPCRs is that the receptors generate some signal that activates an endogenous GPCR, which in turn catalyzes G protein activation.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…The first proposal is that the receptors possess the ability to directly catalyze heterotrimeric G protein guanine nucleotide exchange (32). Consistent with this, several groups have reported that heterotrimeric G protein subunits co-precipitate with the IGF-1 and insulin receptors (22,23,25) or have demonstrated that small peptides derived from the insulin and IGF-2 receptors promote a mastoparan-like acceleration of GTP exchange on purified heterotrimeric G proteins in vitro (31,(33)(34)(35). The second model advanced to explain heterotrimeric G protein-dependent signaling by non-GPCRs is that the receptors generate some signal that activates an endogenous GPCR, which in turn catalyzes G protein activation.…”
mentioning
confidence: 58%
“…In Rat1 fibroblasts, IGF-1-stimulated activation of the ERK1/2 mitogen-activated protein kinase cascade is largely pertussis toxin-sensitive and can be blocked by expressing a G␤␥ subunit sequestrant peptide derived from the C terminus of G proteincoupled receptor kinase 2 (GRK2ct) (19). Similar pertussis toxin-sensitive ERK1/2 activation has been reported in undifferentiated 3T3-L1 cells (20), human intestinal smooth muscle cells (21), primary rat cerebellar granule neurons, and NG-108 neuronal cells (22). In HIRcB cells and 3T3-E1 adipocytes, treatment with pertussis toxin or microinjection of a GRK2ct-glutathione S-transferase fusion protein blocks the mitogenic effect of IGF-1 but not of insulin or EGF (23).…”
mentioning
confidence: 61%
“…39,45 Studies in neuronal and intestinal smooth muscle cells report that activation of the IGF-IR leads to the release of a Gi␤␥ subunit and downstream MAPK activation. 47,48 These data raise the possibility of a similar pathway existing in HCC, activation of which acts to alter HGF signaling to stimulate mitogenesis. Although a promitogenic role for IGF-I/ HGF-SF seems likely in this model of HCC, the pleiotropic nature of IGF-I and HGF-SF raises the possibility of other effects mediated either directly or indirectly.…”
Section: Discussionmentioning
confidence: 97%
“…However, the content of G ai2 with IGF1R was significantly lower in ventricular tissue from the HF þ AF model but not BGP-15-treated mice. G ai has been shown to associate with IGF1R in other tissue/cell types 54,55 , and G ai2 provides protection in the heart 56,57 . Thus, this could represent one mechanism by which BGP-15 is mediating protection via IGF1R in the HF þ AF model.…”
Section: Discussionmentioning
confidence: 99%